The Mapping of the German Language Competence of German Students at Pattimura University - Kalvin Karuna (International Journal of Advanced Science and Technology, 2020)
One of graduates’ profile of German Language Study Program, Pattimura University, is to produce German language teachers with minimum B1 level of language competence. In order to ensure the achievement of these language competencies, an evaluation needs to be carried out as a basis for curriculum review. The questions in this study are (a) whether the German Language Competency of Students have reached level B1 and (b) how is the distribution of German language competence of students. The aim of this study is to describe the German language competence of students at German Language Education Study Program. The research data was obtained through language skills tests which included reading comprehension, listening, writing and speaking. The data collected were tabulated according to their respective skills, followed by description. The findings of this study are (a) the overall German language competency of students of the German Language Education Study Program at Pattimura University, has not yet reached B1 level,(b) the distribution of German competency is uneven. The lowest students’ competency is reading, where no students reached the passing grade. Followed by listening; 16% achieved passing grade, writing; 26% and speaking; 68%. The findings notify that German study programs must improve their teaching and learning or review the curriculum.